2005
DOI: 10.1158/0008-5472.can-05-2372
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Protein Kinase Cι Is an Oncogene in Human Non–Small Cell Lung Cancer

Abstract: Protein kinase C (PKC) isozymes have long been implicated in carcinogenesis. However, little is known about the functional significance of these enzymes in human cancer. We recently showed that the atypical PKC (aPKC) isozyme PKCiota is overexpressed in human non-small cell lung cancer (NSCLC) cells and that PKCiota plays a critical role in the transformed growth of the human lung adenocarcinoma A549 cell line in vitro and tumorigenicity in vivo. Here we provide compelling evidence that PKCiota is an oncogene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
299
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(311 citation statements)
references
References 31 publications
(44 reference statements)
11
299
1
Order By: Relevance
“…We have shown that PKCi is an oncogene that is activated by amplification in squamous cell carcinoma of the lung (Regala et al, 2005a). We have also shown that PKC plays a critical role in transformed growth (Zhang et al, 2004;Regala et al, 2005b), but does not appear to function as a survival gene. In contrast, our present results show that Evi1 is a survival gene in human colon cancers that have undergone amplification of the 3q26 locus.…”
Section: Discussionmentioning
confidence: 95%
“…We have shown that PKCi is an oncogene that is activated by amplification in squamous cell carcinoma of the lung (Regala et al, 2005a). We have also shown that PKC plays a critical role in transformed growth (Zhang et al, 2004;Regala et al, 2005b), but does not appear to function as a survival gene. In contrast, our present results show that Evi1 is a survival gene in human colon cancers that have undergone amplification of the 3q26 locus.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequent interaction of PAR1 with 14-3-3 dissociates PAR1 from the plasma membrane, thereby preventing the distribution of PAR1 to the apical membrane domain. Gene amplification and elevated activity of aPKC, which downregulates PAR1 functions, have also been reported in ovarian, lung and colon carcinomas (Murray et al, 2004;Eder et al, 2005;Regala et al, 2005).…”
Section: Function Of Par1 In Carcinogenesismentioning
confidence: 92%
“…In glioblastoma, PKCi represses apoptosis and promotes invasion (Baldwin et al, 2006(Baldwin et al, , 2008. PKCi also has a key role in the pathogenesis of lung, ovarian and pancreatic cancer (Eder et al, 2005;Regala et al, 2005;Zhang et al, 2006). Several previous studies have provided evidence for a role for the PI-3-kinase pathway in senescence.…”
Section: Introductionmentioning
confidence: 99%